2017
DOI: 10.1097/ico.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

CTG18.1 Expansion in TCF4 Increases Likelihood of Transplantation in Fuchs Corneal Dystrophy

Abstract: Purpose Fuchs dystrophy is the leading indication for corneal transplantation in the United States. A CTG18.1 trinucleotide repeat in TCF4 correlates with increased severity in Fuchs dystrophy; however, quantitative estimates of increased transplantation risk, including effects of age and gender, are unclear. Methods In a tertiary institution clinical practice, 574 participants were enrolled in a longitudinal study of Fuchs dystrophy after slit-lamp biomicroscopy confirmed significant central guttae and/or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…We and others have previously shown that CTG18.1 expansion may affect clinical severity, 8 , 14 including an increase in the need for cornea transplantation. 15 Therefore, the data reported here may help clarify reports of decreased transplantation rates among African Americans with Fuchs' dystrophy. 5 …”
Section: Discussionmentioning
confidence: 57%
“…We and others have previously shown that CTG18.1 expansion may affect clinical severity, 8 , 14 including an increase in the need for cornea transplantation. 15 Therefore, the data reported here may help clarify reports of decreased transplantation rates among African Americans with Fuchs' dystrophy. 5 …”
Section: Discussionmentioning
confidence: 57%
“…We evaluated the association of the CTG18.1 repeat status (expanded or nonexpanded) with the type of surgical procedure (whether it involved corneal endothelium), as the CTG trinucleotide repeat expansion status in patients with FECD can increase the likelihood of corneal transplantation. 33,34 We found a tendency between the involvement of corneal endothelium in the surgical procedure and the CTG trinucleotide repeat expansion status in our FECD cohort, but it did not reach the level of significance (Table 6). We did not find an association between the FECD grade and CTG trinucleotide repeat expansion status.…”
Section: Diagnostic Performance Of Tcf4 Gene Variantsmentioning
confidence: 72%
“…The strongest genetic association with FECD is with an intronic (CTG·CAG) n trinucleotide repeat (TNR) expansion in the third intron of the transcription factor 4 ( TCF4 ) gene. 1 8 Unaffected individuals typically have 12 to 18 TNR repeats, but up to 79% of individuals with FECD have an unstable CTG·CAG repeat length greater than 50. 1 While nearly all TNR expansion diseases to date are directly linked to rare neurologic or neuromuscular disorders, FECD is the first eye disease associated with a TNR expansion.…”
mentioning
confidence: 99%